Reproducibility of Biomolecular Corona Experiments: A Primer for Reliable Results. (12th December 2022) - Giulimondi, Francesca; Quagliarini, Erica; Digiacomo, Luca; Renzi, Serena; Palmieri, Valentina; Papi, Massimiliano; Pozzi, Daniela; Caracciolo, Giulio
Abstract: The biomolecular corona is a key component controlling the identity of nanomaterials in physiological environments. Studies aimed at identifying factors shaping the biomolecular corona have proliferated in the last decade but have been performed by research groups with different backgrounds. Efforts made within the scientific community to guarantee the reproducibility of experimental data have identified protocol standardization as an indispensable step for advancing knowledge in this arena. To contribute to fulfill this gap, here the relevance of interoperator variability in biomolecular corona studies and the benefits arising from automated systems usage are explored. Moreover, the role of molecular crowding during nanoparticle‐biofluid incubation and the effect of washing the pellet during corona isolation are thoroughly investigated. It is believed that the findings will help researchers enhance the accuracy of experimental design and reporting. Abstract : To achieve standardization of the procedures that are commonly applied in the analysis of the biomolecular corona, manifold factors should be carefully taken into account, including interoperator variability, manual versus automatic mixing, incubation protocols, and the number of washing steps for the corona isolation.